Paths to a reserve currency: Internationalization of the renminbi and Its implications - Yiping Huang; Daili Wang; Gang Fan (Asian Development Bank Institute (ADBI), 2014)
In this paper we try to address the question of what could help make the renminbi a reserve currency. In recent years, the authorities in the People's Republic of China (PRC) have made efforts to internationalize its currency through a two-track strategy: promotion of the use of the renminbi in the settlement of cross-border trade and investment, and liberalization of the capital account. We find that if we use only the quantitative measures of the economy, the predicted share of the renminbi in global reserves could reach 12%. However, if institutional and market variables are included, the predicted share comes down to around 2%, which is a more realistic prediction. By reviewing experiences of other reserve currencies, we propose a three-factor approach for the PRC authorities to promote the international role of the renminbi: (i) increasing the opportunities of using renminbi in the international community, which requires relatively rapid growth of the PRC economy and continuous liberalization of trade and investment; (ii) improving the ease of using renminbi, which requires depth, sophistication, and liquidity of financial markets; and (iii) strengthening confidence of using renminbi, which requires more transparent monetary policy making, a more independent legal system, and some political reforms. In general, we believe that the renminbi's international role should increase in the coming years, but it will take a relatively long period before it plays the role of a global reserve currency.
Keywords: F30; F33; F36; F42; 330; RMB internationalization; reserve currency; anchor currency; capital account openness